The Interplay of Boredom and Academic Procrastination among University Students - Munaf, Sara; Yousaf, Sadia; Tahir, Muhammad (ACADEMIA International Journal for Social Sciences, 2025)
This study explores the link between boredom and academic procrastination among students at the University of Sargodha in Pakistan. The study involved a survey using Likert-scale questions, targeting 150 students from various disciplines and backgrounds. Data is analysed to determine the relationship between boredom and procrastination in academic settings, focusing on avoidance of academic tasks, focus on deadlines, and timidity to begin tasks. The survey contains demographic information and Likert scale items assessing students’ perceptions of boredom and self-reported academic procrastination. The study employs statistical techniques like correlation and regression analysis. Analyses are performed across different sub-groups (gender, age, academic course, family background and type of academic course) to explore any differences. The key findings of the study highlight a strong association between academic procrastination and boredom, with higher levels of boredom being associated with increased procrastination. Moreover, the study highlights the complexity of this relationship and the importance of considering individual and environmental factors. The implications of this research are important for educators, counselors and policymakers interested in enhancing higher education outcomes by reducing procrastination. By shedding light on the intricate link between academic procrastination and boredom of the University of Sargodha students, this research contributes to our understanding of student engagement and motivation.